Educational simulation and gaming: interactivity perspective. (25th January 2012) - Sabry, Khaled
This paper investigates simulation and gaming technologies in relation to the 'interactivity' and 'learning interaction' concepts. This paper reviews literature in the fields of educational simulation and gaming (ESG) and human–computer interaction. It particularly focuses on the commonalities between ESG and the interactivity notion. It explores the rationale behind using simulation and gaming for education and looks at different factors that may affect the planning and design decisions including, learning goals and levels, types and modes of learning interactions, levels of interactivity and guidelines, individual differences and pedagogical aspects. The investigation shows close linkage between ESG and core interactivity factors in relation to interactive learning systems design. This paper concludes with recommendations and reflection on future research in the area of ESG.